Teaching Arabic in Malaysia using Higher Education 4.0 technologies / Airil Haimi Mohd Adnan - Mohd Adnan, Airil Haimi (2021)
The Arabic language is a popular third language course at Malaysian universities, especially for the majority Malay-Muslim students. Because of their familiarity with the Islamic faith, they prefer this language as a third language, and also as a means to improve their religious piety by deepening their understanding of Islam through the Al-Qur'an. Nonetheless, the teaching and learning of Arabic seems to depend largely on the conventional 'chalk and talk' system, accompanied by constant vocabulary drills and memorisation process, relative to the English language and indeed other third languages. Given that 'Generation Z' (young people born between 1995 to 2015) and 'Generation Alpha' (children born between 2011 and 2025) are digital residents who are familiar with, and prefer to be educated by, technology, this is a serious concern. Based on data gathered from a mass online survey involving nearly 250 respondents, this study explores the above issue. Both Likert-scale closed statements and open questions were included in the survey questionnaire that sought the thoughts and expectations of respondents about Arabic language teaching in the Higher Education 4.0 era using state-of-the-art educational technology apps and tools